Genetic Differentiation, Diversity, and Drug Susceptibility of Candida krusei - Gong, Jie; Xiao, Meng; Wang, He; Kudinha, Timothy; Wang, Yu; Zhao, Fei; Wu, Weiwei; He, Lihua; Xu, Ying-Chun; Zhang, Jianzhong (Frontiers in Microbiology, 2018)
Candida krusei is a notable pathogenic fungus that causes invasive candidiasis, mainly due to its natural resistance to fluconazole. However, to date, there is limited research on the genetic population features of C. krusei. We developed a set of microsatellite markers for this organism, with a cumulative discriminatory power of 1.000. Using these microsatellite loci, 48 independent C. krusei strains of clearly known the sources, were analyzed. Furthermore, susceptibility to 9 antifungal agents was determined for each strain, by the Clinical and Laboratory Standards Institute broth microdilution method. Population structure analyses revealed that C. krusei could be separated into two clusters. The cluster with the higher genetic diversity had wider MIC ranges for six antifungal agents. Furthermore, the highest MIC values of the six antifungal agents belonged to the cluster with higher genetic diversity. The higher genetic diversity cluster might have a better adaptive capacity when C. krusei is under selection pressure from antifungal agents, and thus is more likely to develop drug resistance.